Xingxing Ductile Iron Pipes : transforming the management control system in time of crisis - McFarlan, F. Warren (SAGE knowledge. Cases., 2016)
It was March 2011. The earth was awakening with new life. For Zhang Tongbo, the general manager of Xinxing Ductile Iron Pipes Co. in Handan China (roughly 200 kilometers southeast of Beijing) (hereinafter referred to as Xinxing Pipes) it was springtime in his heart as well. Xinxing Pipes, a large state-owned enterprise with over 17,000 employees and 26.7 billion RMB in assets, was already the industry leader and its largest manufacturer in several product categories. The annual report for 2010 released on March 2nd continued to demonstrate outstanding performance. Additionally, the company's future development looked promising. Nevertheless, Zhang Tongbo was concerned. How could the company continue to take advantage of its large scale, without losing flexibility? This case study answers this question.